Réponses

  • Utilisateur Brainly
2014-09-06T14:38:55+02:00
A= 4x + (2x + 1)(5x - 3)
A= 4x + 10x² - 6x + 5x - 3
A= 10x² + 3x - 3

B= (x + 3)(y + 9) + 10x - 7
B= xy + 9x + 3y + 27 + 10x - 7
B= xy + 19x + 3y + 20

C= (3x - 5)(7 + 6x) - (7 + x)
C= 21x + 18x² - 35 - 30x - 7 - x
C= 18x² - 10x - 42

D= 5x + 1 - (x + 4)(x - 9)
D= 5x + 1 - (x² - 9x + 4x - 36)
D= 5x + 1 - x² + 9x - 4x + 36
D= - x² + 10x + 37
merci tu me sauves la vie! mais comment tu fais?
De rien! =) c'est à dire ?
pour savoir faire tout ca.. ?
2014-09-06T14:42:49+02:00
A = 4x + (2x + 1) (5x - 3)
A = 4x + 10x² - 6x + 5x - 3
A = 10x² + 4x + 5x - 6x - 3
A = 10x² + 3x - 3

B = (x + 3) (y + 9) + 10x - 7
B = xy + 9x + 3y + 27 + 10x - 7
B = xy + 19x + 3y + 20

C = (3x - 5) (7 + 6x) - (7 + x)
C = 21x + 18x² - 35 - 30x - 7 -  x
C = 18x² + 21x - 30x -  x - 35 - 7
C = 18x² - 10x - 42

D = 5x + 1 - (x + 4) (x - 9)
D = 5x + 1 - (x² - 9x + 4x - 36)
D = 5x + 1 - x² + 9x - 4x + 36
D = - x² + 5x + 9x - 4x + 1 + 36
D = - x² + 10x + 37